The Implementation of Character and Example Values KH. Ahmad Dahlan on PKn Subjects in Class V of Muhammadiyah 19 Primary School - Kurnia Wati, Dewi (Berpusi Publishing, 2023)
This research was motivated by the application of character and exemplary values applied at the Muhammadiyah 19 Medan Denai Elementary School. By implementing learning according to KH. Ahmad Dahlan with application to students at SD Muhamamdiyah 19. This research uses the classroom action research (PTK) method which takes teachers and students as research objects. Data collection techniques use observation. The concept of education according to Kh.Ahmad Dahlan in Muhammadiyah prioritizes practice or action rather than material. Based on the researcher's observations, discussion and analysis of the data described in the previous chapter, it can be concluded that. Teacher activities in cycle I have received a teacher activity score of 80 with very good criteria (A). So the researcher did not continue to carry out cycle II because the score obtained already met the criteria for success in teacher activity, namely 70. The object of the research was class V with a total of 17 students. Student activities in cycle I and cycle II experienced an increase in the completeness of student activities. Based on the results of observations of student activities in terms of student character values in Civics subjects, according to Ahmad Dahlan, students are still said to be lacking, because in the first cycle it shows that 10 students (59%) completed and 7 students (41%) did not complete. ). Classically, student activities in cycle I did not meet the minimum completion criteria, namely 70. In cycle II, it showed that 14 students (82%) completed and 3 students (18%) did not complete